Polar Patrol Balloon experiment in Antarctica during 2002-2003 - Kadokura, Akira; Yamagishi, Hisao; Sato, Natsuo; Ejiri, Masaki; Hirosawa, Haruto; Yamagami, Takamasa; Torii, Shoji; Tohyama, Fumio; Nakagawa, Michio; Okada, Toshimi; Bering, Edgar A. (National Institute of Polar Research, 2002)
P(論文) The first scientific campaign of the Polar Patrol Balloon (PPB) experiment (1st-PPB) was performed at Syowa Station in Antarctica during 1990-1991 and 1992-1993. Based on the fruitful results of the 1st-PPB experiment, the next campaign (2nd-PPB) will be carried out in the austral summer of 2002-2003. This paper summarizes the 2nd-PPB experiment. Four balloons in total will be launched to make astrophysics observations (1 balloon) and upper atmosphere physics observations (3 balloons). The first payload will carry a very sophisticated instrument that will observe primary cosmic-ray electrons in the energy range of 10 GeV - 1 TeV. The payloads of the latter 3 flights are identical to each other. They will be launched in as rapid a succession as weather conditions permit to form a cluster of balloons during their flights. Such a "Balloon Cluster" is suitable for observing the temporal evolution and spatial distribution of various phenomena in the various magnetospheric and ionospheric regions and their boundaries that the balloons will traverse during their circumpolar trajectory. The expected flight duration of each balloon is 20 days. Observation data will be obtained mainly by a satellite communication system with a much higher temporal resolution than that used in the 1st-PPB experiment. departmental bulletin paper